Eye-to-eye or face-to-face? Face and head substitution for co-located augmented reality - Kullmann, Peter; Schell, Theresa; Botsch, Mario; Latoschik, Marc Erich (Frontiers in Virtual Reality, 2025)
In co-located extended reality (XR) experiences, headsets occlude their wearers’ facial expressions, impeding natural conversation. We introduce two techniques to mitigate this using off-the-shelf hardware: compositing a view of a personalized avatar behind the visor (“see-through visor”) and reducing the headset’s visibility and showing the avatar’s head (“head substitution”). We evaluated them in a repeated-measures dyadic study (N = 25) that indicated promising effects. Collaboration with a confederate with our techniques, compared to a no-avatar baseline, resulted in quicker consensus in a judgment task and enhanced perceived mutual understanding. However, the avatar was also rated and commented on as uncanny, though participant comments indicate tolerance for avatar uncanniness since they restore gaze utility. Furthermore, performance in an executive task deteriorated in the presence of our techniques, indicating that our implementation drew participants’ attention to their partner’s avatar and away from the task. We suggest giving users agency over how these techniques are applied and recommend using the same representation across interaction partners to avoid power imbalances.